The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1093/oxfordjournals.humrep.a137736
|View full text |Cite
|
Sign up to set email alerts
|

The detrimental influence of functional ovarian cysts during in-vitro fertilization cycles

Abstract: Reviewing 780 in-vitro fertilization (IVF) cycles, where buserelin was commenced in the preceding luteal phase and human menopausal gonadotrophin on day 4 of the ensuing menses, 53 cycles were identified with sonolucent cysts (30-50 mm diameter). Of the latter 53 cycles, the serum oestradiol was significantly greater on day 4 in 22 cycles abandoned for poor follicular development than in 31 cycles which proceeded to oocyte retrieval (P less than 0.05). Of the 31 cycles proceeding to oocyte retrieval, nine had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The impressive transient flare-up effect of GnRH-a on immature antral follicles with LH surge inhibition has been the most frequent explanation (5)(6)(7)(8). The presence of an ovarian cyst in IVF cycles has been studied frequently in terms of its effect on the clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impressive transient flare-up effect of GnRH-a on immature antral follicles with LH surge inhibition has been the most frequent explanation (5)(6)(7)(8). The presence of an ovarian cyst in IVF cycles has been studied frequently in terms of its effect on the clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Such cysts may impair folliculogenesis in such a way as to decrease the pre-ovulatory follicle numbers and their quality (2,3). In addition to the studies showing the negative effect of the cysts that appear during GnRH-a administration, other studies have concluded that the functional cysts have no effect on the IVF outcome (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Functional ovarian cysts associated with elevated basal oestradiol levels have been shown to exert a detrimental influence on IVF cycles 16 . Functionally active follicular ovarian cysts occur in at least 5% of IVF cycles when GnRH agonists are used for pituitary desensitisation 17 .…”
Section: Aetiology Of Poor Responsementioning
confidence: 99%
“…Functionally active follicular ovarian cysts occur in at least 5% of IVF cycles when GnRH agonists are used for pituitary desensitisation 17 . If gonadotrophins are commenced in the presence of a functionally active cyst there is a high likelihood that the response to gonadotrophins will be impaired 16 .…”
Section: Aetiology Of Poor Responsementioning
confidence: 99%
See 1 more Smart Citation